Learning Method For Local Identity Through Traditional Food In Tulungagung â€œAyam Lodhoâ€ - Ellyzabethania, Gladera Ellyzabethania; Khusyairi, Jhony Alfian; Rosyidah, Usma Nur Dian (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research aims to look into the traditional food of Tulungagung. Ayamlodho is a traditional Tulungagung dish that is very popular among the locals. AyamLodho is also served with urap-urap and has a distinctive grilled and spicy sauce. AyamLodho became popular among Tulungagung residents as the main course menu at special events. The purpose of this research is to examine the meaning of AyamLodho as well as the meaning of the word Lodho. This study employs a qualitative approach. In-depth interviews, observation, document studies, literature studies, and recording sources are all used to collect data. Functional analysis is a method for deciphering the meaning of Ayamlodhofood.The goal of this review is to analyze the meaning of the traditional food "AyamLodho" using this symbolic model so that the meaning obtained is the meaning of Bronislaw Malinowski. Malinowski's theory is a progression of functionalism in terms of methods for describing the various functional relationships of cultural elements in a living social system, with a focus on cultural objects and tradition. The role of the reader is the most important object of research in this theory, and it is the role of the reader who will trigger various views on the meaning of AyamLodho's traditional food. According to the findings, the meaning of Ayam lodho with a functionalism approach is an expression of gratitude for the people of Tulungagung Regency. As for this theory, cultural and traditional sociological heritage are not biological heritage. Beliefs or religion, traditional customs, and social structures are examples of social heritage forces that influence and shape the personality born into the community.